Honour and shame as keys to the interpretation of Malachi - Botha, Phil J. (Old Testament essays, 2001)
The relationship between the different role players in the book of Malachi is defined by the text itself predominantly in terms of the social values of honour and shame. It is suggested in this paper that the values of honour and shame, and the rituals by which they were displayed, form the key to the interpretation of the book. The success of the covenantal relationship between Yahweh and his people was dependent on the mutual recognition and display of the values of honour and shame by the covenant partners. In the book, the people of post-exilic Judah complain that Yahweh has not complied with their expectations of being honoured by him; while Yahweh in turn complains that their complaints and disrespectful actions are dishonouring him. The book suggests that restoration of the relationship between Yahweh and his people would be dependent upon restoration of the people's respect for Yahweh and that this would result in restoration of honour for his followers.